The Influence of Advertising Creativity, Credibility, Lack of Irritation, Informativeness, And Entertainment on Consumer Attitudes Towards Brand on Gojek Advertising - R.A Adenia Kumala Adzani; Premananto, Gancar Candra (Universitas Airlangga, 2023)
This study examines the role of advertising creativity, credibility, lack of irritation, informativeness, and entertainment on consumer attitude toward the brand on Gojek X Ariel NOAH #CepetanGoSendInstant on YouTube. This research was conducted using a quantitative approach with a survey method. The data was obtained through an online survey using Google Forms to 256 respondents who are YouTube social media users in Indonesia with a minimum age of 18 years and have seen Gojek advertisement CepetanGoSendInstant